1991
DOI: 10.1177/039219219103915602
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Contextual Emotion The Grounds for “Supra-Rationality”

Abstract: Anne:] &dquo;I can't, I'm in the depths of despair. Can you eat when you are in the depths of despair?&dquo; &dquo;I've never been in the depths of despair, so I can't say,&dquo; said Marilla. &dquo;Weren't you? Well did you ever try to imagine you were in the depths of despair?&dquo; &dquo; No, I didn't.&dquo; &dquo;Then I don't think you can understand what it's like. It's a very uncomfortable feeling indeed. When you try to eat a lump comes right up in your throat and you can't swallow anything, not even if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…68 Corruption is considered to be one of the greatest factors contributing to the stunted growth experienced by many African nations. 69 But with increased transparency and growing foreign investment it is crucial that the United States continue to police corruption through measures like the FCPA.…”
Section: Corruption and Bribery In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…68 Corruption is considered to be one of the greatest factors contributing to the stunted growth experienced by many African nations. 69 But with increased transparency and growing foreign investment it is crucial that the United States continue to police corruption through measures like the FCPA.…”
Section: Corruption and Bribery In Africamentioning
confidence: 99%
“…75 Africa has been associated with a large number of FCPA violations therefore, U.S. companies continually have to weigh the possible economic benefits of business in Africa against potential FCPA pitfalls. 76 …”
Section: A the Impact Of Corruption And Bribery On Development Efformentioning
confidence: 99%
“…197 Although there is some disagreement regarding whether clinicians can accurately predict future dangerousness, 198 most experts believe that they cannot. 199 Studies have shown that clinical predictions are not much more accurate than chance. 200 One potential problem is that factors that would seem to be intuitively linked to risk are not.…”
Section: J An Important Caveat Regarding Underreportingmentioning
confidence: 99%
“…201 Nor are general psychological problems, 202 alcohol abuse, or the accused's being abused as a child predictors for reoffending. 203 Factors related to the crime, like low empathy for the victim and degree of sexual contact, are also unassociated with recidivism. 210 Generally, when courts find the probative value of prior sexual misconduct low, it is because they focus on the dissimilarities between the prior bad acts and the charged conduct.…”
Section: J An Important Caveat Regarding Underreportingmentioning
confidence: 99%
“…Here, much of contemporary Western culture is taken to regard emotions as highly naturalised dimensions of Blood Ties 319 experience-emotions are pre-rational, instinctive, pre-cognitive and individualised. 19 Because of their essentialised treatment in most popular and academic discourse, emotions like hope are infused with authenticity and derive considerable rhetorical value as a consequence. It is, we might say, hard to argue against the authenticity and genuineness of aspirations couched in affective terms like hope and desire.…”
Section: On Hope and Affectivitymentioning
confidence: 99%